ANALISIS MINAT BELAJAR SISWA MTs KELAS VIII DALAM PEMBELAJARAN MATEMATIKA MELALUI APLIKASI GEOGEBRA - Hanipa, Akbar (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2019)
This study was conducted to analyze the learning interest of class VIII MTs students in mathematical learning through Geogebra application. The research method used descriptive qualitative with a population of all MTs students in West Bandung Regency. The sample used was 28 students of class VIII-A MTs Al-Barry. The instrument used is the Learning Interest Scale with 20 statements that have positive and negative responses about learning using the Geogebra application. The learning interest scale is used to look for responses from respondents to the learning interest of junior / MTs students in statistical material whose learning uses Geogebra applications. The results of this study indicate that students' interest in learning in statistical material with Geogebra application media shows positive results with average responses showing a strong category with a percentage of 69,46%. The average is obtained from data on each indicator of student learning interest.